Building Harmony In Diversity: Exploring Masnun Tahir's Perspective on Multicultural Fiqh - Arif Sugitanata; Suud Sarim Karimullah; Siti Khamidatus Sholikhah; Siti Aminah (JURISY: Jurnal Ilmiah Syariah, 2023)
The primary purpose of this study is to explore the views and thoughts of Muslim scholar Masnun Tahir on how to develop a fiqh framework that supports harmony in culturally and religiously diverse societies. This study carries a qualitative approach by analyzing Masnun Tahir's writings, especially in multicultural fiqh and understanding religious pluralism. The research method involves the analysis of texts and critical content of works relevant to the theme of multiculturalism and harmony in the view of Masnun Tahir. The findings of this study indicate that Masnun Tahir's views on multicultural fiqh inherently carry the values of inclusiveness and respect for the rights of individuals regardless of religious and cultural background. Through this perspective, Masnun Tahir seeks to build bridges between diverse groups of people to maintain harmony and diversity. The concept of multicultural fiqh Masnun Tahir's social and humanitarian perspective has illustrated that multicultural fiqh goes beyond the application of Islamic law in diverse societies. It is a vision of how religion can be a source of inspiration in creating inclusive, tolerant, and just societies. Multicultural fiqh contains universal human values that transcend religious and cultural boundaries, potentially shaping harmonious societies and global peace. Implementing this concept involves changing people's mindsets and behavior and creating an inclusive and tolerant environment.